2014
DOI: 10.1159/000358009
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reported Skin Morbidities and Health-Related Quality of Life: A Population-Based Nested Case-Control Study

Abstract: Background: Impaired dermatological health-related quality of life (HRQoL) has been observed in hospital-based studies, but little is known on a population-based level. Objective: To investigate self-reported dermatological HRQoL in the general population. Methods: Hidradenitis suppurativa, psoriasis, pimples, hand rash or atopic eczema were identified using questionnaires in a 15,177 person population sample. A nested case-control study of 180 cases and 259 controls was made using the Dermatology Life Quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 41 publications
2
37
0
3
Order By: Relevance
“…HS influences patients' lives in many ways [15] . HS patients experience several emotional reactions, including anger, sadness, anxiety, and depression.…”
Section: Discussionmentioning
confidence: 99%
“…HS influences patients' lives in many ways [15] . HS patients experience several emotional reactions, including anger, sadness, anxiety, and depression.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have previously demonstrated a significant reduction in quality of life (QoL), using Dermatology Life Quality Index (DLQI), among patients with HS (5,6). In fact, a study found that the mean DLQI scores for patients with HS (8.9) were higher than previously reported for other skin diseases, such as alopecia (8.3), acne (7.5) and psoriasis (7.0) (6).…”
Section: Short Communicationmentioning
confidence: 93%
“…In a survey of patients receiving oral GC therapy for 60 days or more, 60 % of participants reported skin changes that were bothersome [ 13 ]. Skin changes can have substantial psychological effects and therefore affect patients' HRQoL [ 14 ]. Current EULAR recommendations do not advocate routine monitoring of skin thinning for low-dose oral GCs taken for less than 6 months [ 2 , 15 ].…”
Section: Nature and Pathophysiology Of Glucocorticoid Toxicities Skinmentioning
confidence: 99%